Anorexia Nervosa - Zipfel, Stephan; Stengel, Andreas; Giel, Katrin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Anorexia nervosa is a common eating disorder affecting several functions of the body. Although our knowledge of the underlying mechanism has increased, therapeutic options are still limited. This Special Issue discusses several aspects of anorexia nervosa and covers a broad range of topics from the bench to the bedside.